Challenges And Resilience in Multicultural Teaching: Unpacking the Cultural Barriers Among Filipino Educators in Southeast Asia in Times of Covid 19 Pandemic - Quitolbo, Ruben (Langue (Journal of Language and Education), 2024)
This study explored the experiences of Filipino educators in Southeast Asia on the challenges they encountered and how they tend to be resilient while teaching in a multicultural teaching environment amid the COVID 19 pandemic. The research utilized the qualitative descriptive phenomenological design in analyzing the narratives of the informants. A total of eight participants were selected via purposive sampling and were from each of the nine (9) Southeast Asian countries. Semi structured interview was the main tool for data gathering while results were thematically analyzed and presented. Findings showed that Filipino educators teaching a multicultural class were confronted with diverse, unique, and encompassing challenges but still majority have found their niche in their place of employment regardless of the difficulties, anxiety brought by the pandemic, or uncertainty about whether they will be rehired. Most were resolved to continue to teach for as long as opportunities present themselves to them. From the narratives of the Filipino educators, the following themes were gathered as to teaching interruptions namely difficulties handling the virtual classroom and confronting the challenges of teaching and learning during the pandemic. With regards to challenges on differentiated instructions, emphasizing the differentiated learning assessment dilemma and uncovering the challenges of differentiated learning instruction were the most dominant themes. For the challenges on instructional emphasis, the participants revealed that managing frustrations and expectations along with teaching in a difficult learning environment as their overarching experience. Furthermore, with regards to behavior in classroom to address teacher resiliency and teacher efficacy beliefs to address teacher resiliency in a multi-cultural classroom finding revealed the following themes namely a nurturing figure in the multi-cultural classroom, promoting acceptance and tolerance within the classroom, being a caring teacher in the classroom and establishing one’s place in a multi-cultural classroom. For the most part, most Filipino educators find working with multicultural students whether in their own country or overseas challenging due to the diverse cultural make-up of their students and the pandemic but at the same time fulfilling. Further development of cultural competencies should be included in the curriculum and made part of the courses to be taken in college.